Development of EM‐CCD‐based X‐ray detector for synchrotron applications. Issue 17 (1st August 2014) - Tutt, J.H.; Hall, D.J.; Soman, M.R.; Holland, A.D.; Warren, A.; Connolley, T.; Evagora, A.M.
Abstract : A high speed, low noise camera system for crystallography and X‐ray imaging applications is developed and successfully demonstrated. By coupling an electron‐multiplying (EM)‐CCD to a 3:1 fibre‐optic taper and a CsI(Tl) scintillator, it was possible to detect hard X‐rays. This novel approach to hard X‐ray imaging takes advantage of sub‐electron equivalent readout noise performance at high pixel readout frequencies of EM‐CCD detectors with the increase in the imaging area that is offered through the use of a fibre‐optic taper. Compared with the industry state of the art, based on CCD camera systems, a high frame rate for a full‐frame readout (50 ms) and a lower readout noise (<1 electron root mean square) across a range of X‐ray energies (6–18 keV) were achieved.